Disaster Management Awareness among Teachers in a Town of Haryana Shivaliks: A Case Study of Morni Hills: Assessing the Knowledge and Awareness of Teachers in Disaster Management (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Disaster Management Act of 2005 introduced a paradigm still, from erstwhile response centric syndrome to a proactive prevention, mitigation and preparedness approach. The emphasis has shifted from response to preparedness in India. The onus for making people aware les on educational institutions. So it is inevitable to equip teachers with essential knowledge so that the coping capacity and the resilience of the community can be enhanced.Morni Hills lies in the Panchkula district of Haryana. These are offshoots of Shivaliks and are located on mountainside, at 1220 meters above mean sea level. The geo climate zone in which Morni hills is located is highly vulnerable to various natural as well as manmade disasters such as earthquake, landslide, floods and forest fires.The current study is an effort to evaluate the awareness levels of teachers teaching under graduate students in colleges of Morni Hills towards various disasters. For the purpose of this study questionnaire was prepared and personal interviews were conducted. The results reveal that the teachers do not meet the satisfactory level of awareness about the disaster management and the essential knowledge of the disaster management should be improved.